1993
DOI: 10.4141/cjas93-026
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and biochemical changes following an acute stress in control and somatostatin-immunized pigs

Abstract: following an acute stress in control and somatostatin-immunized pigs. Can. J. Anim. Sci. 73: 241-252. Sixteen Yorkshire pigs (49 + 2 kg BW) were used. Half (4M, 4F) were immunized against somatostatin (SRIF-IMM) and the other half against its conjugated protein (BSA-IMM) at 10, 12 and 14 wk of age. At the age of 19 wk, half the animals were subjected to 5 min of snare restraint, followed 2 dlater by the other half; on both days the unstressed animals were used as controls. On

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
(15 reference statements)
5
9
0
2
Order By: Relevance
“…The WBC counts in our study were within the range reported in Wild Boar or feral pigs or even in domestic pigs, although a wider total WBC count range was found by these authors. This difference in the ranges could be due to either preexisting subclinical disease generally associated with leukocytosis and an increase in segmented neutrophils, or stress induced by transport or captivity prior to sampling which may have also caused stress‐related leukocytosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The WBC counts in our study were within the range reported in Wild Boar or feral pigs or even in domestic pigs, although a wider total WBC count range was found by these authors. This difference in the ranges could be due to either preexisting subclinical disease generally associated with leukocytosis and an increase in segmented neutrophils, or stress induced by transport or captivity prior to sampling which may have also caused stress‐related leukocytosis.…”
Section: Discussionsupporting
confidence: 78%
“…It has been shown that the stress response associated with chemical or physical restraint may influence hematology and serum chemistry variables . Thereby, acute stress associated with physical struggling or snare restraint and application of anesthetic agents induced marked changes in a series of hematologic and biochemical variables . In addition, it has been reported that stress can influence the immune response in domestic pigs .…”
Section: Discussionmentioning
confidence: 99%
“…The decreased levels of urea suggest enhanced nitrogen retention in clenbuterol-treated animals, even though no difference was seen between the two groups at slaughter. Increased urea levels after the acute stress response are probably due to increased protein catabolism associated with muscle damage during transport (DUBREUIL et al, 1993), and are in part due to enhanced cortisol output (FOSTER and MACGARRY, 1988).…”
Section: Transport and Slaughterhouse Procedures Effectsmentioning
confidence: 99%
“…CPK significantly increased at slaughter and was higher in clenbuterol-treated than in control pigs, as also found by WARRISS et al (1990) in salbutamol-tremed pigs. CPK released into the blood is an indicator of muscle metabolism and increases as a result of stress (DUBREUIL et al, 1993) especially in stresssusceptible pigs (POLTARSKY et al, 1989). WARRISS et al (1990) suggested that there should be a higher propensity to produce pale, soft and exudative meat in BAA-treated animals.…”
Section: Transport and Slaughterhouse Procedures Effectsmentioning
confidence: 99%
“…Moreover, the similarity in the prevalence of gastric ulcers and the lack of any treatment effect on the haematological and biochemical profiles do not suggest that transient stray voltage was causing stress in the pigs (O'Brien, 1986;Dubreuil et aL, 1989). Moreover, the similarity in the prevalence of gastric ulcers and the lack of any treatment effect on the haematological and biochemical profiles do not suggest that transient stray voltage was causing stress in the pigs (O'Brien, 1986;Dubreuil et aL, 1989).…”
Section: Performancementioning
confidence: 99%